Recent views on/from Peronism in Argentine fiction cinema - Dillon, Alfredo (2020)
The article offers a formal and narrative analysis of two recent biographical films about Peronism: Juan y Eva (Paula de Luque, 2011) and Iron Gate. The Exile of Perón (Víctor Laplace and Dieguillo Fernández, 2012). Both films are read in relation to the political climate they share: that of the third Kirchner government in Argentina. Built from two opposing narrative aesthetics –a minimalist post-epic on the one hand, a discursive recovery of the Peronist epic on the other– the two films, however, share an idealizing view of the figures of Juan Domingo and Eva Perón.